In Praise of Cybernetics - Andreas Rumpfhuber (Footprint)
In the late 1950s the Quickborner Team developed a cybernetics-inspired design methodology for organisations, focusing on information flow, with the aim to fully automate administrative labour and to make the organisation constantly adaptable to unpredictable future challenges. Participant analysis allowed them to quantify communication in an organisation and with that envision a new kind of office space. The so-called Bürolandschaft (office landscape), seemingly-endless, chaotic looking interiors, would allow for efficient information flow. One significant aspect of Bürolandschaft design is the non-hierarchic organisation of workers in teams that were bound to quantified decision-making processes, yet addressed as experts, scientists and creatives, ultimately conditioning them to participate voluntarily in reaching the organisation’s goal without questioning